PENGUATAN KAPABILITAS DIGITAL UKM BATIK CANTING KHAS GEMPOL KABUPATEN PASURUAN MELALUI PEMBINAAN DAN PENDAMPINGAN TRANSFORMASI BISNIS DIGITAL - Nizar, Muhammad; Jamhuri, M.; Rakhmawati, Antin (Jurnal Abdi Insani, 2024)
The Batik Canting Khas Gempol SMEs in Pasuruan Regency face challenges in adopting digital technology to expand their market and enhance competitiveness. Low digital literacy is the main barrier. This program is designed to provide training and assistance for digital business transformation. The aim of this activity is to increase digital capabilities and motivate SME members to more actively utilize digital technology. This program uses a participatory action research model involving training, workshops, seminars, and individual consultation sessions to enhance participants' digital skills. As a result, 20 participants attended the training and workshops, with an average attendance rate of 97%. Significant improvements were observed in the participants' digital understanding, with an average post-test score of 90% compared to a pre-test score of 50%. About 95% of participants successfully created digital content, and 90% were able to use social media platforms for promotion. Within 2 months after the training, 70% of participants reported an average online sales increase of 30%. This program successfully improved the digital capabilities of Batik Canting Khas Gempol SMEs, demonstrating that external support and guidance are effective in empowering SMEs to undergo digital transformation.